Pharmacological Potential of Cilostazol for Alzheimer’s Disease - Ono, Kenjiro; Tsuji, Mayumi (Frontiers in Pharmacology, 2019)
Alzheimer’s disease (AD), a slow progressive form of dementia, is clinically characterized by cognitive dysfunction and memory impairment and neuropathologically characterized by the accumulation of extracellular plaques containing amyloid β-protein (Aβ) and neurofibrillary tangles containing tau in the brain, with neuronal degeneration and high level of oxidative stress. The current treatments for AD, e.g., acetylcholinesterase inhibitors (AChEIs), have efficacies limited to symptom improvement. Although there are various approaches to the disease modifying therapies of AD, none of them can be used alone for actual treatment, and combination therapy may be needed for amelioration of the progression. There are reports that cilostazol (CSZ) suppressed cognitive decline progression in patients with mild cognitive impairment or stable AD receiving AChEIs. Previously, we showed that CSZ suppressed Aβ-induced neurotoxicity in SH-SY5Y cells via coincident inhibition of oxidative stress, as demonstrated by reduced activity of nicotinamide adenine dinucleotide phosphate oxidase, accumulation of reactive oxygen species, and signaling of mitogen-activated protein kinase. CSZ also rescued cognitive impairment and promoted soluble Aβ clearance in a mouse model of cerebral amyloid angiopathy. Mature Aβ fibrils have long been considered the primary neurodegenerative factors in AD; however, recent evidence indicates soluble oligomers to initiate the neuronal and synaptic dysfunction related to AD and other protein-misfolding diseases. Further underscoring the potential of CSZ for AD treatment, we recently described the inhibitory effects of CSZ on Aβ oligomerization and aggregation in vitro. In this review, we discuss the possibility of CSZ as a potential disease-modifying therapy for the prevention or delay of AD.